Rancang Bangun Simulasi Robot Beroda untuk Pengiriman Barang di dalam Gedung berbasis Metode Particle Filter - Reza Budi Pratikto; Eko Setiawan; Dahnial Syauqy (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The F building at the Faculty of Computer Science, Universitas Brawijaya hold 12 floors and has separate rooms which arranged in several dividers between rooms where each floor in the building has different functions and jobs, in a words, a coordination for logistical assistance or file delivery is indispensable. Current document delivery activities generally depend on the workforce of employees, and are quite time consuming and cause a lack of concentration on employees doing their own work. Therefore in this study the researcher will focus on discussing the design of a wheeled robot for logistics delivery in the building. The system were designed in a simulation used ROS-Gazebo to run the robot and the method used to run the robot were using a Particle Filter. The robot's particle filter works by localized its position by spreading a number of particles around it so that the particles can represent the robot's position. Particle Filter test can be done by determining a certain number of particles, testing the accuracy of its position and computation time for 5 times. In later testing, it was found that the number of particles that had high accuracy was at 50 particles with an average computation time of 292.08 ms for each number of particles tested. The results show that the time and the number of particles are optimum in the F9.3 building environment located at the Faculty of Computer Science, Universitas Brawijaya.